Navigating Potential Hype and Opportunity in Governing Marine Carbon Removal - Boettcher, Miranda; Brent, Kerryn; Buck, Holly Jean; Low, Sean; McLaren, Duncan; Mengis, Nadine (Frontiers in Climate, 2021)
As the technical and political challenges of land-based carbon dioxide removal (CDR) approaches become more apparent, the oceans may be the new ‘blue’ frontier for carbon drawdown strategies in climate governance. Drawing on lessons learnt from the way terrestrial carbon dioxide removal emerged, we explore increasing overall attention to marine environments and mCDR projects, and how this could manifest in four entwined knowledge systems and governance sectors. We consider how developments within and between these ‘frontiers’ could result in different futures – where hype and over-promising around marine carbon drawdown could enable continued time-buying for the carbon economy without providing significant removals, or where reforms to modelling practices, policy development, innovation funding and legal governance could seek co-benefits between ocean protection, economy and climate.